Pengaruh Zeolit Dan Abu Cangkang Telur Sebagai Bahan Stabilisasi Terhadap Nilai CBR Tanah - Henrianto Masiku; Yusri Anugerah Manapa Ambabunga; Ermitha Ambun Rombe Dendo; Rudolf Masiku (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Soil is the place where construction is built, thats why the soil must have a high bearing capacity. Clay is a fine-grained soil that has low bearing capacity. its necessary to improve it so that the construction can be built and provide a longer service life. Soil improvement to increase the bearing capacity of the soil can be done by stabilization. Soil stabilization using mixed materials is expected to minimize unfavorable soil properties. This research aims to evaluate the impact of using eggshell ash and zeolite as a stabilizer on the bearing capacity of the soil, in this case the CBR value of the soil. The method used is an experimental study in the laboratory. Sample testing was carried out at the UKI Toraja Civil Engineering Geotechnical Laboratory. Stabilizing materials include egg shells and natural zeolites. Egg shells and natural zeolite are burned until then ground and filtered using sieve No. 200 (0.075 mm) until ash is obtained. The variations of eggshell ash and natural zeolite used in this research were 0%, 4%, 6% and 8% of the dry weight of the soil and variations of eggshell ash of 4% of the dry weight of the soil. From the test results obtained, it can be seen that the combined use of zeolite and eggshell ash as a clay soil stabilization material can increase the CBR value of the soil in variations of Zeolite 4% and ACT 4%, Zeolite 6% and ACT 4% as well as Zeolite 8% and ACT 4%. – respectively 8.0 %, 25.3 % and 36.4 for soil without stabilization material.